Amorphous Coatings and Surfaces on Structural Materials. Issue 1 (2nd January 2016) - Joshi, Sameehan S.; Katakam, Shravana; Singh Arora, Harpreet; Mukherjee, Sundeep; Dahotre, Narendra B.
Abstract : Metallic glasses show a unique combination of high strength, excellent corrosion, and wear resistances because of their amorphous structure having a short-range order. In spite of excellent properties, the application of metallic glasses is restricted because of their inherent limitations in the bulk form, including limited tensile ductility. Using metallic glasses as the coatings for structural applications is an attractive way of taking advantage of their superior properties. Additionally, metallic glass-based composites having crystalline phases embedded in a amorphous matrix have also shown improved properties. Thus, metallic glasses can be synthesized as the coatings or subjected to surface modification to provide functionally superior surfaces. This article is a review of metallic glass-based coatings and surface modification of metallic glasses to achieve functionally superior surfaces for structural applications. Essential theoretical concepts were discussed which influence the processing. Common ways of processing along with the influence of various processing parameters were explored. Some non-conventional techniques which emerged as a result of continued efforts were also taken into account. Corrosion and wear properties of these materials along with the underlying mechanisms were discussed in detail. Focus was given to the recent product level applications explored in the open literature. Current challenges in the field were reviewed and guidelines for the future developments were provided.